The Mode of Speech Acts in the Film â€œTanah Surga Katanyaâ€ by Danial Rifki - Hayati, Itsnaini Nur; Rustono, Rustono (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to find the form of the speech mode in the film "Tanah Surga Katanya" by Danial Rifki. This qualitative-descriptive study used a data collection technique that was free to engage in conversation. The source of the research data is the utterances in the film "Tanah Surga Katanya" by Danial Rifki. The data in this research is some utterances in the film "Tanah Surga Katanya" by Danial Rifki which is thought to contain pragmatics in the form and mode of speech. Methods of data analysis use the equivalent method. The presentation of the results of data analysis using informal data presentation. The results showed that the form of speech used in the film is direct and indirect, with a tendency to use direct forms. The modes found in direct speech are declarative, imperative, and interrogative. The speech modes used in the indirect form include declarative-imperative, interrogative-declarative, and interrogative-imperative. This research is important for the society so that it can be used as a trigger to be critical and creative in addressing the types of speech modes in everyday life.